On the Convergence of Fourier Series with Orthogonal Polynomials inside and on the Closure of a Region - Abdullayev, F. G.; Küçükaslan, M. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We study the rate of convergence of Fourier series of orthogonal polynomials over an area inside and on the closure of regions of the complex plane.